Bio-based Lubricants: Progress in Research - Yinan Hao; Kai Zhang; Jingwen Wang; Renfei Wang; Guo Zhang; Rao Duan; Mengyao Li; Zhiyuan Ren; Shuo Wang; Ximing Wang (BioResources)
Biomass is widely distributed, inexpensive, and easily obtainable. As a transportable and storable organic carbon source, biomass has significant advantages in terms of sustainability, environmental friendliness, resource richness, and versatility. The utilization of biomass resources instead of traditional non-renewable energy is advantageous for addressing issues related to energy, the environment, and product diversity. The conversion of biomass into energy chemicals serves as an effective complement to current energy products. In addition to their role as a protective agent, lubricants play a crucial role in machinery operation. This paper provides a comprehensive review of various plant-based lubricant-based oil synthesis technologies with promising applications, such as olefin metathesis, cross-lactone, plant sugar fermentation, and C-C coupling. It also covers modification techniques including additive, chemical, and biological modifications. Technical process of each synthesis and modification method is summarized, as well as the physical and chemical properties of the obtained lubricating oil products. This technology also overcomes limitations of traditional vegetable oil modification methods. A thorough analysis is provided on the performance and process economics of plant-based lubricant base oil synthesis technology to guide industrial development in this area. Additionally, it includes an analysis of future trends in plant-based lubricant synthesis technology.